Front Cover: Advanced Materials Based on Polymers and Ionic Liquids (Chem. Rec. 4/2018). Issue 4 (19th April 2018) - Kitazawa, Yuzo; Ueno, Kazuhide; Watanabe, Masayoshi
Abstract : The cover picture shows composites of ionic liquids and well‐designed polymers or colloids applicable to advanced materials ranging from electrolytes for electrochemical devices to photonic materials to photo‐healing materials. See the Personal Account by Y. Kitazawa, K. Ueno, and M. Watanabe (DOI:10.1002/tcr.201700041 ).